Endovascular Management of Peripheral Vascular Trauma - Johnson, Chatt A. (Thieme Medical Publishers, 2010)
Endovascular interventions (EVIs) are an important adjunct to open surgical management of peripheral vascular injuries. In appropriate situations, EVIs decrease operative time, estimated blood loss, and iatrogenic complications when compared with similar surgical cohorts by limiting surgical dissection in traumatized operative fields. In situations where definitive repair is not possible with EVIs, endovascular techniques permit control of hemorrhage or damage and facilitate open surgical repair. EVIs for peripheral vascular injury have proven effective in three anatomic regions: the neck, subclavian, and lower-extremity regions. The interventional radiologist should become familiar with the physical and personnel resources in the area preferred by the consulting trauma team to minimize unnecessary delays when acute intervention or angiography is requested. Clinical and radiographic surveillance for patency and compliance with antiplatelet or anticoagulation therapy is essential but has historically been poor in trauma patients.